Hand Therapy Protocol after Arthroscopic Reconstruction of the Scapholunate Ligament Based on the Pathomechanics and Neuromuscular Control of the Scapholunate Joint - Esplugas, Mireia; Artigau, Josep Maria Sole (Revista Iberoamericana de Cirugía de la Mano, 2023)
Objective This study aimed to assess the efficacy of a hand therapy protocol following the arthroscopic reconstruction of the dorsal scapholunate ligament according to the Corella technique.Methods We implemented a protocol lasting less than 3 months, divided into seven therapeutic phases, based on the pathomechanics and neuromuscular control of the scapholunate joint. We provided clear guidelines for the clinical evaluation of the patient.Results We observed a significant improvement in pain, strength, and mobility in all studied patients 6 months after surgery.Conclusions The proposed sequential protocol seems an effective strategy for hand rehabilitation following arthroscopic reconstruction of the scapholunate ligament. This protocol has positive implications for the clinical practice and could be a new hand therapy standard.
Keywords: hand therapy; scapholunate arthroscopy; carpal stability; scapholunate protocol; scapholunate rehabilitation; corella's technique